2017
DOI: 10.1017/s0950268817002217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of boiling and chlorination on the quality of stored drinking water and childhood diarrhoea in Indonesian households

Abstract: SUMMARY We compared the impact of a commercial chlorination product (brand name Air RahMat) in stored drinking water to traditional boiling practices in Indonesia. We conducted a baseline survey of all households with children <5 years in four communities, made 11 subsequent weekly home visits to assess acceptability and use of water treatment methods, measured Escherichia coli concentration in stored water, and determined diarrhoea prevalence among children <5 years. Of 281 households surveyed, boiling (83%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Though not statistically significant, children whose family did not treat their water were 1.2 times (p = 0.057) more likely to be infected by IPIs. Chlorination is less expensive, less time consuming and provides residual disinfection against recontamination and significantly reduces diarrhea [54]. However, due to the smell and taste [55], only a few families use chlorination in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though not statistically significant, children whose family did not treat their water were 1.2 times (p = 0.057) more likely to be infected by IPIs. Chlorination is less expensive, less time consuming and provides residual disinfection against recontamination and significantly reduces diarrhea [54]. However, due to the smell and taste [55], only a few families use chlorination in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for the variation in anaemia prevalence could be due to differences in maternal education [57] concomitant childhood malaria superinfection [55], family income [58], drinking water source [51], personal-hygiene [68] and STH infections [54,57]. For example, the high anaemia rate in the studies such as Tanzania, Kenya, Senegal, Uganda, south Ethiopia, was due to concomitant malaria infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The household practice of regularly adding chlorine to the cistern provided an additional protective effect in decreasing high fecal contamination levels after the DWTP. In limited resource settings, home chlorination interventions have been associated with dramatically reduced rates of self‐reported diarrhea (Fagerli et al, ; Mengistie, Berhane, & Worku, ). In contrast, households that reported that they washed their cistern within the last month, or even less than a year ago had high levels of fecal contamination, which were not present in households that washed their cistern over a year ago or had never washed it.…”
Section: Discussionmentioning
confidence: 99%
“…Low strength of evidence due to low intervention uptake which confers difficulty in evaluating the impacts of intervention [54] • Significant association between education intervention and reduction in diarrheal incidence as seen in RCTs [39,56,79,102] The majority of the reviewed studies demonstrated positive relationship between primary preventive interventions on diarrhea incidence and disease transmission by ad-dressing WBD associated health risks, however, there is a lack of assessed literature that quantifies the extent of the efficacy of such interventions on disease reduction. In the case of water treatment, many studies conferred a well-established link between less contaminated household drinking water and reduction in diarrhea risk, but not the effectiveness of WBD reduction and associated health outcomes, such as mortality, within the community [29,41,51,55,59,64,70,71,83,85,100,101].…”
mentioning
confidence: 99%